Halal Tourism Based on Islamic Economy Perspective of Hadith - Fathan Budiman; Naqiyah Mukhtar (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
This research is motivated by the tendency of a literal understanding of hadith texts regarding halal tourism based on shari’a economics. This study aims to analyze and describe the hadith texts that form the basis for the concept of halal tourism. Using a literature review as the method, a qualitative approach will be employed to achieve this, with content analysis as the interpretation method utilized in this research. The study results indicate that the application of the hadith text requires contextualization to avoid limiting the concept of universal halal tourism with a shari’a label, particularly about shari’a economic imperatives. This study also shows that Indonesia is a conducive country, thanks to its moderate understanding that links Islamic texts with universal and local values, making it an ideal center for global halal tourist destinations. It is important to note that halal tourism is based on three fundamental principles: good intentions as the primary foundation, good service as a spirit, and wise spending (thrifty) as the primary value.